Single-component transparent alcohol type silicone adhesive and preparation method thereof

By using high refractive-terminal hydroxypolydimethylsiloxane and silazane-treated vapor phase silica in transparent alcohol-type silicone glue, combined with active amino silane capping agent and environmentally friendly titanium complex catalyst, the problems of poor transparency, peak viscosity, poor mechanical properties and corrosiveness are solved, and the silicone glue with high transparency, strength and stability is achieved, which is suitable for the bonding and decoration of building structures.

CN119736064AActive Publication Date: 2025-04-01GUANGZHOU ZHANZHAN NEW MATERIAL IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411914136.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing transparent alcohol-type silicone glue has problems of poor transparency, peak viscosity, poor mechanical properties and corrosiveness, which limits its application in the construction field.

Method used

Nano-grade vapor phase silica treated with high refractive hydroxypolydimethylsiloxane and silazane combined with active amino silane capping agent and environmentally friendly titanium complex catalyst to improve the transparency, stability and mechanical properties of the colloid.

Benefits of technology

It significantly improves the transparency, tensile strength and elongation of break of transparent alcohol silicone glue, extends the shelf life, and ensures the neutral and non-corrosiveness of the sealant, and is suitable for the bonding and decoration of building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, in particular to a single-component transparent alcohol type silicone adhesive and a preparation method thereof. The single-component transparent alcohol type silicone adhesive is prepared from the following components in parts by weight: 90 to 110 parts of hydroxyl-terminated polydimethylsiloxane, 10 to 20 parts of plasticizer, 10 to 20 parts of filler, 2 to 6 parts of end-capping reagent, 3 to 5 parts of cross-linking agent, 1 to 3 parts of catalyst and 0.1 to 1 part of adhesion promoter. The single-component transparent alcohol type silicone adhesive prepared by the invention has the characteristics of high transparency, high strength and high elongation, has higher displacement capacity, can be widely applied to building structure adhesion and attractive adhesion requirements of decoration, and has excellent adhesion, weather resistance and aging resistance to materials such as metal, aluminum and glass; in addition, the mechanical property and the adhesive property of the silicone rubber are slightly influenced by the external environment, so that the transparent alcohol-type structural silicone adhesive is ensured to have good adhesive reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically, to a one-component transparent alcohol-type silicone adhesive and a preparation method thereof. Background Art

[0002] As people's aesthetic requirements for buildings increase, architectural design pays more attention to the integration of lighting and natural elements, such as glass skylights, point curtain walls, full glass curtain walls, transparent material skylight sheds and other architectural structures. These transparent or translucent building structures, home decoration, bathrooms, etc. need to use high-transparency sealants when sealing the joints to achieve a "natural" visual effect.

[0003] The traditional deacidified silicone sealant produces acetic acid as a byproduct during the curing process, which has a pungent odor and is corrosive to metals. It cannot bond cement parts, limiting its application in the construction field. The physical crosslinking agent of the oxime-type sealant releases butanone oxime during the curing process, which is alkaline and corrosive to copper and polycarbonate panels. At the same time, the carcinogenic risks of butanone oxime and organic tin are not environmentally friendly and also have application limitations. Although alcohol-type structural silicone sealants will dealcoholize during curing, and the byproducts are alcohol substances, which are less irritating and environmentally friendly, the following problems still exist:

[0004] (1) Transparency improvement problem: Conventional neutral transparent sealants use ordinary 107 (hydroxyl-terminated polydimethylsiloxane) and hydrophilic fumed silica. The refractive index of ordinary 107 and hydrophilic fumed silica is quite different, resulting in insufficient transparency of the prepared sealant.

[0005] (2) Viscosity peak problem: Alcohol-based adhesive has a viscosity peak during the preparation process, which affects the construction performance and product quality.

[0006] (3) Poor mechanical properties of sealants: The tensile strength and tear strength of transparent alcohol-based sealants are generally poor, and the elongation is also small, which makes the sealants unable to be used in structural bonding and sealing.

[0007] (4) Corrosion problem: Traditional alcohol-based sealants use organic tin or chelated tin as a catalyst. Because of its strong acidity, it will cause PC materials to crack, which will pose safety risks and water leakage risks to the bonding and sealing of home sunrooms. At the same time, it will also react with mirror mercury to cause spot problems. Summary of the invention

[0008] The purpose of the present invention is to provide a one-component transparent alcohol-type silicone adhesive, which is used to solve the technical problems of poor transparency, viscosity peak, poor mechanical properties and corrosiveness of existing transparent alcohol-type silicone adhesives.

[0009] The above technical objectives of the present invention are achieved through the following technical solutions:

[0010] A one-component transparent alcohol-type silicone adhesive comprises, by weight, 90-110 parts of terminal hydroxyl polydimethylsiloxane, 10-20 parts of plasticizer, 10-20 parts of filler, 2-6 parts of end-capping agent, 3-5 parts of cross-linking agent, 1-3 parts of catalyst and 0.1-1 parts of adhesion promoter.

[0011] Preferably, the terminal hydroxyl polydimethylsiloxane is α,β-terminated hydroxyl polydimethylsiloxane, and its molecular structure is HO-Si(CH3)2-O-[(CH3)2SiO] n -Si(CH3)2-OH; at 25°C, its kinematic viscosity is 5000~20000mPa·s, and its refractive index is ≥1.4.

[0012] Preferably, the plasticizer is at least one of branched methyl silicone oil and branched dimethyl silicone oil, and the kinematic viscosity is 100-1000 mPa·s at 25° C. Adding the above silicone oil as a plasticizer can improve the flexibility of the transparent alcohol-type silicone adhesive and increase its elongation at break.

[0013] Preferably, the filler is fumed silica, and the hydrophobic fumed silica post-treated with HMDS (hexamethyldisilazane) has a specific surface area of ​​200 to 250 nm.

[0014] Preferably, the end-capping agent is a highly active amine compound, which is at least one of N-[(triethoxysilyl)methyl]ethylenediamine, N-[(triethoxysilyl)methyl]aniline, and bis[3-(triethoxysilyl)propyl]amine.

[0015] Preferably, the crosslinking agent is a mixture of polymethyltrimethoxysilane and methyltrimethoxysilane in a weight ratio of 3:2.

[0016] Preferably, the catalyst is at least one of tetraisopropyl titanate, tetra-tert-butyl titanate, and trialkoxybutyl phosphate titanate dimer.

[0017] Preferably, the adhesion promoter is a mixture of γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-isocyanatepropyltrimethoxysilane in a weight ratio of 1:1:1.

[0018] Preferably, the preparation method of the adhesion promoter is: slowly add γ-aminopropyltrimethoxysilane to γ-isocyanatepropyltrimethoxysilane, stirring while adding; then slowly add γ-glycidyloxypropyltrimethoxysilane, stirring while adding; after stirring and mixing evenly, heat to 105°C and reflux for 2h, and then cool and store in dry nitrogen.

[0019] The transparent alcohol type silicone glue of the present invention firstly selects a specific base polymer and a plasticizer, and selects silazane-treated fumed silica to make the refractive index of the sealant closer, thereby improving transparency. Secondly, the hydroxyl group at the end of 107 is modified into an alkoxy group using an active amino silane, which not only solves the viscosity peak problem of the sealant, but also prolongs the shelf life, and the alkoxy-terminated 107 can be directly catalyzed by an environmentally friendly colorless to slightly yellow titanium complex, which will not affect the transparency. Further, through the alkoxy modification technology of ordinary 107 glue and silazane-treated fumed silica, the filling amount of fumed silica can be increased from 8% to 20%, thereby improving the mechanical properties of the transparent alcohol type sealant by more than 50%. In addition, by using an environmentally friendly colorless to slightly yellow titanium complex for catalysis, it can be ensured that the sealant is neutral and non-corrosive when cured, and will not cause cracking of the sun room material.

[0020] Another object of the present invention is to provide a method for preparing the aforementioned one-component transparent alcohol-type silicone adhesive, which comprises the following steps:

[0021] S1: Add hydroxy-terminated polydimethylsiloxane and end-capping agent in a power mixing planetary machine in proportion, heat to 80-100°C, and stir to react for 1 hour under vacuum of -0.095MPa; then introduce 20°C cold water to reduce the material temperature to room temperature to obtain end-capped 107 with uniform appearance;

[0022] S2: Add fillers in batches. After they are fully added, shovel the edges and paddle, and stir the reaction under vacuum at -0.095 MPa for 0.5 h.

[0023] S3: Add plasticizer and crosslinking agent into the planetary mixer, and stir and react for 15 minutes under nitrogen protection;

[0024] S4: Add the catalyst and adhesion promoter into the power mixing planetary machine, slowly evacuate and stir for 5 minutes, and continue stirring for 30 minutes after the vacuum reaches -0.095 MPa to obtain the one-component transparent alcohol-type silicone adhesive.

[0025] In summary, the embodiments provided by the above technical solutions of the present invention have the following beneficial effects:

[0026] (1) The one-component transparent alcohol-type silicone adhesive of the present invention adopts high-refractive index end-hydroxyl-terminated 107 adhesive and nano-scale fumed silica treated with silazane to prepare a highly transparent structural silicone adhesive.

[0027] (2) The present invention uses tetraisopropyl titanate, tetra-tert-butyl titanate, and trialkoxy butyl phosphate titanate dimer as catalysts, thereby avoiding the problem of PC material cracking caused by the acidity of the catalyst. At the same time, because a transparent catalyst is used, the transparency of the alcohol-based adhesive is further improved.

[0028] (3) The present invention uses amine compounds to end-cap 107 glue, which improves the stability of the transparent alcohol-type glue and allows its storage period to reach 9 months.

[0029] (4) The present invention uses silazane-treated fumed silica to increase the filling amount of the reinforcing material from the traditional 8% to about 20%, solving the defects of poor mechanical properties and flexibility of alcohol-type transparent adhesive, so that the tensile strength can reach up to 3MPa and the elongation exceeds 400%, expanding its aesthetic needs in building structure bonding and home decoration. DETAILED DESCRIPTION

[0030] In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.

[0031] Example 1

[0032] The present embodiment provides a one-component transparent alcohol-type silicone adhesive, which includes, by weight, 100 parts of terminal hydroxyl polydimethylsiloxane, 15 parts of plasticizer, 15 parts of filler, 4 parts of end-capping agent, 3.5 parts of cross-linking agent, 1.8 parts of catalyst, and 0.8 parts of adhesion promoter.

[0033] Among them, the terminal hydroxyl polydimethylsiloxane has a kinematic viscosity of 5000mPa·s at 25°C and a refractive index of 1.4; the plasticizer is branched methyl silicone oil with a kinematic viscosity of 100mPa·s at 25°C; the filler is hydrophobic fumed silica post-treated with HMDS (hexamethyldisilazane) and has a specific surface area of ​​200-250nm; the end-capping agent is N-[(triethoxysilyl)methyl]ethylenediamine; the cross-linking agent is a mixture of polymethyltrimethoxysilane and methyltrimethoxysilane in a weight ratio of 3:2; the catalyst is tetraisopropyl titanate; and the accelerator is a mixture of γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-isocyanatepropyltrimethoxysilane in a weight ratio of 1:1:1.

[0034] The preparation method of the above-mentioned adhesion promoter is: slowly add γ-aminopropyltrimethoxysilane to γ-isocyanatepropyltrimethoxysilane while stirring; then slowly add γ-glycidyloxypropyltrimethoxysilane while stirring; after stirring and mixing evenly, heat to 105°C for reflux treatment for 2h, and then cool and store in dry nitrogen.

[0035] The above-mentioned one-component transparent alcohol-type silicone adhesive is prepared by the following preparation method, which comprises the following steps:

[0036] S1: Add hydroxy-terminated polydimethylsiloxane and end-capping agent in a power mixing planetary machine in proportion, heat to 90°C, and stir to react for 1 hour under vacuum of -0.095MPa; then introduce 20°C cold water to reduce the material temperature to room temperature to obtain end-capped 107 with uniform appearance;

[0037] S2: Add fillers in batches. After they are fully added, shovel the edges and paddle, and stir the reaction under vacuum at -0.095 MPa for 0.5 h.

[0038] S3: Add plasticizer and crosslinking agent into the planetary mixer, and stir and react for 15 minutes under nitrogen protection;

[0039] S4: Add catalyst and adhesion promoter into the power mixing planetary machine, slowly evacuate and stir for 5 minutes, and continue stirring for 30 minutes after the vacuum reaches -0.095MPa to obtain a one-component transparent alcohol-type silicone adhesive.

[0040] Example 2

[0041] The difference between its raw material composition and that of Example 1 is that the plasticizer is branched methyl silicone oil, and the kinematic viscosity at 25° C. is 1000 mPa·s. The preparation method is the same as that of Example 1.

[0042] Example 3

[0043] The difference between the raw material composition and that of Example 1 is that the kinematic viscosity of the hydroxy-terminated polydimethylsiloxane at 25° C. is 20000 mPa·s. The preparation method is the same as that of Example 1.

[0044] Example 4

[0045] The difference between its raw material composition and that of Example 1 is that the terminal hydroxyl polydimethylsiloxane has a kinematic viscosity of 20000 mPa·s at 25° C. and the plasticizer is branched methyl silicone oil, with a kinematic viscosity of 1000 mPa·s at 25° C. The preparation method is the same as that of Example 1.

[0046] Comparative Example 1

[0047] The difference between the raw material composition and that of Example 1 is that the end-capping agent is omitted. The difference between the preparation method and that of Example 1 is that the hydroxy-terminated polydimethylsiloxane is used as the product of step S1, and then subsequent steps S2 to S4 are performed.

[0048] Comparative Example 2

[0049] The raw material composition thereof is different from that of Example 1 in that the filler is fumed silica that has not been treated with HMDS. The preparation method thereof is the same as that of Example 1.

[0050] Comparative Example 3

[0051] The difference between the raw material composition and that of Example 1 is that the catalyst is dibutyltin bis(ethyl acetoacetate). The preparation method is the same as that of Example 1.

[0052] Comparative Example 4

[0053] The difference between its raw material composition and that of Example 1 is that the end-capping agent is methyltrimethoxysilane. Its preparation method is the same as that of Example 1.

[0054] Comparative Example 5

[0055] Commercially available one-component deoxime silicone adhesive.

[0056] The sealants in the above embodiments and comparative examples were subjected to the following performance tests, and the results are shown in Tables 1 and 2:

[0057] (1) Surface drying time: in accordance with GB / T 13477.5-2003 (Test methods for building sealing materials Part 5: Determination of surface drying time).

[0058] (2) Light transmittance: This is carried out in accordance with GB / T 2410-2008 (Determination of light transmittance and haze of transparent plastics Part 7.2: Spectrophotometer method).

[0059] (3) Tensile strength: tested in accordance with GB / T 13477.8-2003 (Test methods for building sealing materials Part 8: Test of tensile bond strength at 23°C).

[0060] (4) Elongation at break: This is carried out in accordance with GB / T 13477.8-2003 (Test methods for building sealing materials Part 8: Test of elongation at maximum strength at 23°C).

[0061] (5) Adhesion: This test is carried out in accordance with GB / T 13477.8-2003 (Test methods for building sealing materials Part 8: Test of adhesion failure area).

[0062] Table 1 Performance data of the embodiment

[0063]

[0064]

[0065] Table 2 Performance data of comparative examples

[0066]

[0067] It can be seen from the data of the examples and comparative examples in Table 1 and Table 2 that the light transmittance of Examples 1-4 all reached 95%, and Example 4 was superior in tensile strength, elongation at break and high displacement. Compared with Example 1, Example 1 used hydroxy polydimethylsiloxane that was not treated with a capping agent, resulting in insufficient light transmittance, and it was difficult to achieve a "natural" visual effect with highly transparent decorative materials in actual use. Compared with Example 1, Example 2 used fumed silica that was not treated with HMDS, and the tensile strength, elongation at break and displacement level capabilities were all low, and it could not be applied to structural bonding and sealing during actual use. Compared with Example 1, Example 3 used an organic tin catalyst, which first had a carcinogenic risk, was unfriendly to the environment, and was not conducive to improving the transparency of the colloid. Compared with Example 1, Example 4 used a non-highly active amine compound, which was not conducive to the improvement of the transparency, tensile strength and elongation at break of the colloid. Comparing Comparative Example 5 with Example 1, Comparative Example 5 is far lower than Example 1 in terms of transparency, tensile strength and displacement level performance.

[0068] In summary, the one-component transparent alcohol-type silicone adhesive provided by the present invention has the characteristics of high transparency, high strength, high elongation, and high displacement capacity, and can be widely used in the bonding of building structures and the aesthetic bonding requirements of decoration. It has excellent bonding, weather resistance, and aging resistance to materials such as metal, aluminum, and glass; in addition, the mechanical properties and bonding properties of silicone rubber are less affected by the external environment, ensuring that the transparent alcohol-type structural silicone adhesive has good bonding reliability performance.

[0069] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. One-component transparent alcohol-type silicone adhesive, characterized in that: Calculated by weight, it includes 90-110 parts of terminal hydroxyl polydimethylsiloxane, 10-20 parts of plasticizer, 10-20 parts of filler, 2-6 parts of end-capping agent, 3-5 parts of cross-linking agent, 1-3 parts of catalyst and 0.1-1 parts of adhesion promoter.

2. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The terminal hydroxyl polydimethylsiloxane is α,β-terminal hydroxyl polydimethylsiloxane, and its molecular structure is HO-Si(CH3)2-O-[(CH3)2SiO] n -Si(CH3)2-OH; at 25°C, its kinematic viscosity is 5000~20000mPa·s, and its refractive index is ≥1.

4.

3. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The plasticizer is at least one of branched methyl silicone oil and branched dimethyl silicone oil.

4. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The filler is fumed silica, and the hydrophobic fumed silica is post-treated with HMDS, and its specific surface area is 200-250nm.

5. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The end-capping agent is a highly active amine compound, which is at least one of N-[(triethoxysilyl)methyl]ethylenediamine, N-[(triethoxysilyl)methyl]aniline, and bis[3-(triethoxysilyl)propyl]amine.

6. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The crosslinking agent is a mixture of polymethyltrimethoxysilane and methyltrimethoxysilane.

7. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The catalyst is at least one of tetraisopropyl titanate, tetra-tert-butyl titanate, and trialkoxybutyl phosphate titanate dimer.

8. The one-component transparent alcohol-type silicone adhesive according to claim 1, characterized in that: The adhesion promoter is a mixture of γ-aminopropyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-isocyanatepropyltrimethoxysilane.

9. The one-component transparent alcohol-type silicone adhesive according to claim 8, characterized in that: The preparation method of the adhesion promoter is as follows: slowly add γ-aminopropyl trimethoxysilane to γ-isocyanate propyl trimethoxysilane, stirring while adding; then slowly add γ-glycidyl ether oxypropyl trimethoxysilane, stirring while adding; after stirring and mixing evenly, heat to 105° C. and reflux for 2 hours, and then cool and store in dry nitrogen.

10. The method for preparing a one-component transparent alcohol-type silicone adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Add hydroxy-terminated polydimethylsiloxane and end-capping agent in a power mixing planetary machine in proportion, heat to 80-100°C, and stir to react for 1 hour under vacuum of -0.095MPa; then introduce 20°C cold water to reduce the material temperature to room temperature to obtain end-capped 107 with uniform appearance; S2: Add fillers in batches. After they are fully added, shovel the edges and paddle, and stir the reaction under vacuum at -0.095 MPa for 0.5 h. S3: Add plasticizer and crosslinking agent into the planetary mixer, and stir and react for 15 minutes under nitrogen protection; S4: Add the catalyst and adhesion promoter into the power mixing planetary machine, slowly evacuate and stir for 5 minutes, and continue stirring for 30 minutes after the vacuum reaches -0.095 MPa to obtain the one-component transparent alcohol-type silicone adhesive.

Citation Information

Patent Citations

  • Single-component bonding sealing type silicone adhesive for solar battery assembly

    CN102746486A

  • Alkoxy-terminated polysiloxane polymer and preparation method thereof

    CN104558612A

  • Dealcoholized organosilicon sealant with excellent yellowing resistance and preparation method thereof

    CN111334245A

  • Single-component dealcoholized room-temperature vulcanized silicone sealant and preparation method thereof

    CN112143451A

  • Transparent high-strength self-leveling one-component sealant and preparation method thereof

    CN115710482A